Legal Certainty and Legal Protection For Victims of Catcalling In Indonesia: A Critical Analysis of The Sexual Violence Crime Law And Maqāṣid Al-Sharī'ah - Nurfadilah Djafar; Rusdiyanto Puluhulawa; Irl an Puluhulawa; Rasham Armab Saikhu (Yayasan Cendekia Gagayunan Indonesia, 2026)
Catcalling is one of the most common forms of non-physical sexual harassment in public spaces, yet legal protection for victims in Indonesia still faces various obstacles. Although Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence recognizes non-physical sexual harassment as a crime, there is no regulation that explicitly defines catcalling, resulting in normative ambiguity, legal uncertainty, and differences in interpretation in its enforcement. This study aims to analyze the legal regulations regarding catcalling in Indonesian positive law, identify obstacles to legal protection for victims, and examine it from the perspective of maqāṣid al-syarī'ah. The study uses a normative legal research method with a statutory, conceptual, comparative, and Islamic legal approach. Primary, secondary, and tertiary legal materials are analyzed qualitatively through grammatical, systematic, and teleological interpretations. The results show that the absence of a clear legal definition of catcalling means that legal protection does not fully fulfill the principles of legal certainty, particularly lex certa and lex stricta, so that law enforcement still relies on the interpretation of officials. Furthermore, difficulties in proving, gender bias in law enforcement, a culture of victim blaming, and the normalization of verbal sexual harassment further weaken protection for victims. From the perspective of maqāṣid al-syarī'ah, catcalling contradicts the principles of Hifz al-'Ird (protection of honor), Hifz al-Nafs (protection of life), and Hifz al-Karamah (protection of human dignity). This study offers a normative reconstruction of the regulation of catcalling through harmonization between the TPKS Law and the Criminal Code, while integrating positive law with Islamic legal principles to strengthen legal certainty and increase the effectiveness of legal protection for victims of verbal sexual harassment.